(untitled) (ItalianoLinguadue, 2023)
L’articolo si propone come un resoconto di un esperimento didattico svolto presso un’associazione di volontariato nell’Alto Vicentino che organizza corsi di italiano L2. Ad una classe di donne migranti sono state proposte delle attività basate sui task, un approccio comunicativo attento ai bisogni pragmatici degli apprendenti. Real life before exercise. Bringing tasks into voluntary teaching, a case in the Alto Vicentino area This article proposes a report about a teaching experiment developed into an organization of volunteers located in the Alto Vicentino area that offers classes of Italian language as a second language (L2). With a focus on learners’ attitude and needs, task-based activities were carried out in a class of only female learners.